Embellish Kitchen Design / Norliana Baharil … [et al.] - Baharil, Norliana; Ramli, Risya Raheeda; Mohamad Kasim, Suzila; Mohd Taib, Normaisarah (2004)
Name of the business We have agreed to choose Embellish Kitchen Design as the name of our business. Embellish Kitchen Design means our business's innovation inline with an up to date design. We think that the mention name is suitable for our goals as well as to give the spirit in running the business. Nature of the business Embellish Kitchen Design is a partnership type of business. We choose this concept because partners as such run this type of business they share the amount of capital, profit and lost. The advantages of it are any loses are divided into the number of shareholders. Moreover, the sum of money to be paid base on the shareholders equity. Industry Profile The business develops an expertise over designing and constructing kitchen especially in Shah Alam. Our clients are residents around Shah Alam. Our design philosophy is to ensure that each and every project is design and schedule with due consideration to all design criteria to create the best solution it is certainly our aim to provide effective and flexible design. The aim of the business is to provide services of the highest professional standard, seeking to improve human environment through high quality of work and services.